Corporate capital budgeting and CEO turnover - Hornstein, Abigail S. (Journal of Corporate Finance, 2013)
When a firm has minimal agency and informational asymmetry problems it should make efficient capital budgeting decisions. Many firms over-invest prior to CEO turnover, halt investments in the period surrounding the turnover, and then greatly increase their level of expenditures. Empirical analysis of the cross-sectional and inter-temporal variation in the quality of firms' corporate capital budgeting decision reveals that the impact of CEO turnover is asymmetric between under- and over-investing firms, and this complements the larger literature using average firm-wide performance measures. Firms are more likely to have forced turnovers when there is more over-investment prior to the turnover, and these firms make more efficient investment decisions subsequently. Board influence is largely insignificant prior to a CEO turnover but is consistently associated with higher levels of investment subsequently.